Skim Bantuan Zakat Asnaf Mualaf: Satu Analisis Kontemporari di Malaysia - Azman, A.R; Irwan, M.S; Nuradli Ridzwan Shah, M.D; Wan Mohd. Fazrul Azdi, W.R; Rose Irnawaty, Ibrahim; Norlina Ismail; Mahazan Abdul Mutalib @ Talib (Universiti Sains Islam Malaysia, 2024)
Journal of Fatwa Management and Research, 6(1), 167-191.